Rhodamine B-containing silica films from TEOS precursor: Substrate surface effects detected by photoluminescence - da Silva, Alison Abreu; Flor, Juliana; Davolos, Marian Rosaly [UNESP] (Elsevier B.V., 2007)
This work presents the study of substrate surface effects on rhodamine B-containing silica films obtained from TEOS (tetraethylorthosilicate) acid hydrolysis. Soda-lime glass substrates were treated with basic solution under different reaction times and temperatures. Rhodamine B-containing silica films were deposited on pre-treated substrates by the spin-coating method. The substrate surface directly affects film morphology and homogeneity. The films are formed by packed silica spheres which protect the dye against acid-base attack. Luminescence spectra present shifts on the dye emission maximum as expected for different pH values on the substrate surface depending on the alkaline treatment. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: silicon oxide; amorphous thin film; photoluminescence; rhodamine B dye